ANALISIS TOKOH DAN PENOKOHAN DALAM NOVEL COLORS IN THE SKY KARYA TENDERLOVA - Rizky, Maulia Ananda; Effendy, Chairil; Wartiningsih, Agus (Universitas Tanjungpura, 2026)
This study aims to describe and analyze the characters and characterization in Tenderlova's novel Colors in The Sky, and to implement them in the form of teaching modules for Indonesian language learning in high school. Using qualitative methods with a structuralist approach and hermeneutic reading, this study focuses on how the author describes the characters. The results of the study show that the author uses two main techniques: analytical (direct), where characters are explicitly described through their names, appearances, and the author's narration; and dramatic (indirect), which is depicted through dialogue, actions, and interactions between characters. This analysis was applied to the main characters and additional characters who played active roles. In addition, the findings from this study were developed into teaching modules for Indonesian language lessons for 12th-grade students, designed using the Problem-Based Learning (PBL) model and integrating the values of the Pancasila Student Profile. The conclusion of this study confirms that the novel is effective as a relevant and contextual medium for learning literature